2008
DOI: 10.1158/0008-5472.can-07-5183
|View full text |Cite
|
Sign up to set email alerts
|

RASSF1APolymorphism A133S Is Associated with Early Onset Breast Cancer inBRCA1/2Mutation Carriers

Abstract: The tumor suppressor gene RASSF1A regulates cell cycle progression, apoptosis, and microtubule stability and is inactivated by promoter methylation in f50% of breast cancers. It has been shown previously that the polymorphism A133S in RASSF1A reduces its ability to regulate cell cycle progression and this polymorphism is associated with an increased risk of breast cancer. We analyzed the frequency of RASSF1A A133S in 190 Caucasian women without breast cancer and 653 patients with breast cancer including 138 BR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 18 publications
3
49
1
1
Order By: Relevance
“…It is interesting that the A133S polymorphism was found to localize to microtubules (Figure 6b), lacked the ability to associate with a-and g-tubulin, but associated with btubulin (Figure 6c-e), and promoted tumor formation similar to the E246K in an accelerated manner when compared with wild type and vector control cells. A133 is part of the recognition site for the ATM kinase, 131 SQAE, and numerous polymorphisms have been identified within the ATM-phosphorylation site in lung, ovarian and breast cancer patients (Gao et al, 2008;Hamilton et al, 2009). Recently, it was demonstrated that S131 of the ATM site can be phosphorylated using ionizing radiation and requires phosphorylation of S131 to signal p73, induce cell death and suppress colony formation (Hamilton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that the A133S polymorphism was found to localize to microtubules (Figure 6b), lacked the ability to associate with a-and g-tubulin, but associated with btubulin (Figure 6c-e), and promoted tumor formation similar to the E246K in an accelerated manner when compared with wild type and vector control cells. A133 is part of the recognition site for the ATM kinase, 131 SQAE, and numerous polymorphisms have been identified within the ATM-phosphorylation site in lung, ovarian and breast cancer patients (Gao et al, 2008;Hamilton et al, 2009). Recently, it was demonstrated that S131 of the ATM site can be phosphorylated using ionizing radiation and requires phosphorylation of S131 to signal p73, induce cell death and suppress colony formation (Hamilton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To date, a few molecular epidemiological studies have investigated the association between the RASSF1A Ala133Ser polymorphism and the cancer risk including breast cancer (Schagdarsurengin et al, 2005;Gao et al, 2008;Bergqvist et al, 2010;Donninger et al, 2011), lung cancer (Kanzaki et al, 2006;Xiao et al 2012), colorectal cancer (Kanzaki et al, 2006), head and neck cancer (Kanzaki et al, 2006), esophageal cancer (Kanzaki et al, 2006;Zhou et al, 2013), renal cell carcinoma (Kawai et al, 2012), hepatocellular carcinoma (Bayram, 2012), gastric cancer (Zhou et al, 2013), prostate cancer (Meyer et al, 2013). However, no consistent conclusion has been drawn.…”
Section: Research Articlementioning
confidence: 99%
“…Besides, genetic effects of the RASSF1A Ala133Ser polymorphism have been shown to vary form one type of cancer to other. Even at the same cancer type, the results are conflicting (Schagdarsurengin et al, 2005;Gao et al, 2008;Bergqvist et al, 2010;Donninger et al, 2011). As a result, the statistical power of an individual study could be very limited for efficient assessment of the RASSF1A Ala133Ser polymorphism.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…RASSF1A is a C-terminal RASSF proteins that represent potential Ras effectors and play important biological roles in cancer progress (Richter et al, 2009). Previous reports found that gene polymorphism in RASSF1A was associated with an early onset of breast tumor (Gao et al, 2008). In addition, RASSF1A could serve as an important diagnostic marker in cancer screening because that methylation of RASSF1A promoter was represented as an early and frequent event in tumorigenesis (Liu et al, 2013).…”
Section: Rassf1a Suppresses Proliferation Of Cervical Cancer Cellsmentioning
confidence: 99%